1995
DOI: 10.1159/000109439
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Autonomic Nerves in the Control of Nasal Circulation

Abstract: Patients suffering from allergic or vasomotor rhinitis usually show nasal mucosal hyperaemia, engorgement, hyperrhinorrhoea and obstruction of the nasal airway. The nasal mucosa is drained by two venous systems which are anatomically and functionally separate. The nasal mucosa receives tone discharges from the sympathetic nerves but not from the parasympathetic nerves. Sympathetic nerve stimulation causes constriction of the resistance vessels via the α -adrenergic mechanism and constriction of the capacitance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 19 publications
(28 reference statements)
1
19
0
4
Order By: Relevance
“…Experimental selective parasympathetic nerve activation in the nasal mucosa of the cat leads to an increase in nasal secretion and vascular congestion 5. Lung found nasal congestion to be related to a withdrawal of sympathetic discharge rather than to an overactivity of the parasympathetic nerves 6. Thus the nasal hypersecretion and stuffiness in our patient is in agreement with the assumption of a lesion of pericarotid sympathetic nerve fibres after carotid artery dissection.…”
supporting
confidence: 88%
“…Experimental selective parasympathetic nerve activation in the nasal mucosa of the cat leads to an increase in nasal secretion and vascular congestion 5. Lung found nasal congestion to be related to a withdrawal of sympathetic discharge rather than to an overactivity of the parasympathetic nerves 6. Thus the nasal hypersecretion and stuffiness in our patient is in agreement with the assumption of a lesion of pericarotid sympathetic nerve fibres after carotid artery dissection.…”
supporting
confidence: 88%
“…Nasal congestion in vasomotor rhinitis seems to be related to a withdrawal of sympathetic discharge and, at least in part, overactivity of the parasympathetic nerves [1,10]. On the other hand, Masini et al [11] reported that vidian nerve stimulation induces histamine release and vasodilatation in patients with vasomotor rhinitis, and Terrahe [12] suggested a role for mast cell degranulation in vasomotor rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent stimulation of the autonomic nerves constricts the capacitance vessels, which signifies that reduced sympathetic activity rather than parasympathetic overactivity may be more important in contributing to nasal congestion. Nonallergic rhinopathies may, therefore, result from loss of sympathetic tone that would normally cause arterial vasoconstriction and decrease in mucosal blood flow [25].…”
Section: Role Of Autonomic Nervous System In Hyperreactivity Of Nasalmentioning
confidence: 99%